2019
DOI: 10.5055/ajdm.2019.0315
|View full text |Cite
|
Sign up to set email alerts
|

Researching natural disaster preparedness through health behavioral change models

Abstract: There have been an increasing number of studies conducted on community preparedness, particularly on changing individual health behaviors in ways that minimizes individual risk to cope with the stress of a natural disaster. A variety of behavioral change theories and models used by disaster academics scrutinize the manner in which individual behavior is sought and transformed into disaster preparedness. This reflects the lack of knowledge about how these models identify certain behaviors regarding natural disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The use of a preparedness model is not new, however. From natural disasters [ 40 ] to terrorist attacks [ 41 ] and disease outbreaks [ 17 , 42 ], preparedness activities have been suggested as a response to threats while trying to understand their impact on individuals and society at large. This is the goal of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a preparedness model is not new, however. From natural disasters [ 40 ] to terrorist attacks [ 41 ] and disease outbreaks [ 17 , 42 ], preparedness activities have been suggested as a response to threats while trying to understand their impact on individuals and society at large. This is the goal of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Individual disaster preparedness requires appropriate knowledge on how to prepare, protect and adapt oneself. However, it also requires a consequential change in behaviour, which is a major field of research [36,37]. A study on sea level rise and flooding suggested that risk communication should integrate information on how to adapt behaviour [38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the research model developed in this study has the potential to be expanded and adjusted for assessing the effectiveness of flood disaster response in other countries prone to natural disasters. Besides that, Samah et al (2019) believed that some TPB improvements are required because several activities associated with disaster preparedness cannot be sorted into only the three primary factors of the TPB model. Hence, this study also includes a moderating variable (trust in public protection) and other additional variables (past experience, perceived severity, and perceived susceptibility) to enhance the existing models.…”
Section: Theoretical Contributionmentioning
confidence: 99%